Analisis Statistik Presepsi Mahasiswa Teknik Kimia Angkatan 2023 Paralel C UPN “Veteran” Jawa Timur Sebagai Kampus Bela Negara Terhadap Efektifitas Rancangan Undang-Undang Perampasan Aset - Maulana Azis Alfahrezi; Muhamad Abiedama Fahrezi; Neo Harlan; Ahmad Rifaldi Prasetia (Jurnal Kendali Teknik dan Sains, 2025)
The Draft Asset Forfeiture Law represents a significant step in combating economic crimes in Indonesia, focusing on non-conviction-based asset recovery. This study aims to analyze the perceptions of Chemical Engineering students (2023 Cohort, Parallel C) at UPN "Veteran" East Java, a designated State Defense Campus, regarding the law's effectiveness. Employing a quantitative approach, data were gathered using a validated Likert-scale questionnaire assessing understanding, potential impacts, and alignment with state defense principles. The findings reveal that the majority of students perceive the draft law as a strategic tool for strengthening justice, reducing corruption, safeguarding public interests, and enhancing governmental integrity. However, some respondents expressed concerns over potential conflicts with human rights and implementation inefficiencies. This research underscores the necessity of harmonizing legislative frameworks with human rights and public trust, emphasizing the role of state defense education in fostering policy support..